2023
DOI: 10.3390/polym15061370
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Inhibition and Osteogenic Potentials of Sr/Zn Co-Doped Nano-Hydroxyapatite-PLGA Composite Scaffold for Bone Tissue Engineering Applications

Abstract: Bacterial infection associated with bone grafts is one of the major challenges that can lead to implant failure. Treatment of these infections is a costly endeavor; therefore, an ideal bone scaffold should merge both biocompatibility and antibacterial activity. Antibiotic-impregnated scaffolds may prevent bacterial colonization but exacerbate the global antibiotic resistance problem. Recent approaches combined scaffolds with metal ions that have antimicrobial properties. In our study, a unique strontium/zinc (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 95 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…6 Nevertheless, they showed great potential to replace the current clinically utilized natural bone grafts and further enhance bone regeneration efficiency. 4,5,7 To realize the expected outcome, the scaffolds must meet different requirements, including adequate mechanical support close to the native bone environment, biodegradability that matches the new bone regeneration rate, and the capability to stimulate vascularization, osteogenesis, and osteointegration, ultimately leading to rapid healing of bone tissue. 8,9 Polycaprolactone (PCL), a synthetic polymeric material, has been widely used for scaffold fabrication due to its exceptional biocompatibility and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Nevertheless, they showed great potential to replace the current clinically utilized natural bone grafts and further enhance bone regeneration efficiency. 4,5,7 To realize the expected outcome, the scaffolds must meet different requirements, including adequate mechanical support close to the native bone environment, biodegradability that matches the new bone regeneration rate, and the capability to stimulate vascularization, osteogenesis, and osteointegration, ultimately leading to rapid healing of bone tissue. 8,9 Polycaprolactone (PCL), a synthetic polymeric material, has been widely used for scaffold fabrication due to its exceptional biocompatibility and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…These major problems usually lead to poor clinical outcomes . 3D-printed synthetic material scaffolds present high reproducibility, interconnectivity, cytocompatibility, bioactivity, and anti-inflammation properties. , However, challenges such as optimal material selection allowing the optimal regeneration effect and cost control based on different methods still exist. Additionally, in-depth mechanism studies on how the material regulates genes and growth factors, as well as the safety of clinical applications, still require further investigation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some segments such as PLGA are often used in tissue engineering [ 59 ]. Many researchers applied PLGA to repair bone tissue [ 60 ], osteochondral [ 61 ] and nerve tissue [ 62 ]. In addition, researchers have noted that the acidic environment produced by the degradation of PLGA or PLA components has a great impact on the immune environment at the implantation site [ 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…HA possesses excellent biocompatibility; however, it has limitations in terms of bactericidal activity and mechanical strength; therefore, postimplant infection and catastrophic failure of 3D-printed scaffolds are the primary causes of postimplant surgery . According to Hassan et al, a huge amount (75%) of postimplant infections are caused by bacterial infections, especially Staphylococcus aureus, which colonize over time to form biofilm, finally resulting in uncurable disease and early failure of the implant. Recent studies showed that the utilization of silver (Ag) as an antibacterial agent improves remodeling by inhibiting infection through damaging cell walls or intracellular organisms (DNA and protein) by attaching Ag + ions to the bacterial cell wall by electrostatic forces. Bee et al synthesized AgNP (AgNO 3 ∼1, 3, and 5 wt %)-decorated HA-based biocomposites, where HA was extracted from chicken bones, and the results showed that AgNO 3 concentration used >1 wt % possessed higher bioactivity in Hank’s balanced salt solution.…”
Section: Introductionmentioning
confidence: 99%